THE ROLE OF THE HEPCIDIN MARKER IN THE DIAGNOSIS OF IRON DEFICIENCY ANEMIA IN PREGNANT WOMEN - Djuraeva, G.T.; Najmutdinova, D.K.; Atakhodzhayeva, F.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Background In Uzbekistan, IDA covers 60% of women of reproductive age, and among deceased mothers this figure reaches 97%-98%. The true prevalence of IDA, especially latent forms, remains underestimated due to the limitations of current screening methods. This confirms the need for a broader and more systematic approach to assessing women’s health in Uzbekistan. Purpose. To evaluate the role of hepcidin and other laboratory markers for the diagnosis and treatment of iron deficiency conditions in pregnant women. Materials and methods. The analysis is based on clinical observations of 330 pregnant women who were diagnosed with grade II iron deficiency anemia (IDA) in the second trimester. Laboratory tests included: Total blood count, ferritin, hepcidin, erythropoietin, OZHSS, HTJ, serum iron. Results. The average hepcidin level in the main group was 9.4±2.3 ng/ml, in the comparative group -10.2±2.5ng/ml, which is significantly lower than the values recorded in the control group (24.6 ± 3.2 ng/ml). The difference between the main and comparative groups is statistically significant (p = 0.037), and when compared with the control group, it is highly reliable (p < 0.001). These values demonstrate a steadily decreased level of regulatory hormone in all women with grade II IDA, regardless of the subsequent therapy regimen. Conclusion. Thus, the increase in ferritin turned out to be the most impressive: from the initial 9.2 mcg/l to 76.4 after 2 weeks and 132.6 by the 4th week, which confirms the rapid and voluminous saturation of the depot. This was accompanied by a parallel increase in NTF (by 25.8%) and the restoration of normal iron transport. Against the background of this restoration of transport accessibility, the expected compensatory rise in hepcidin was recorded, which confirms the activation of reverse regulation — the body begins to "close" absorption and redistribution when the deficiency is eliminated.